Socio-Cultural Awareness Of Food Security Needs And Causes Of Global Hunger Among Women In South- East, Nigeria (Journal of Pharmaceutical Negative Results, 2023)
The main purpose of the study was to investigate the awareness of food security needs and causes of global hunger in South - East, Nigeria. Two research questions and two null hypotheses guided the study. Descriptive survey research design was adopted. The population of the study was 1,271 registered members of women community based organizations in South- East, Nigeria. A sample of 571 registered members was drawn using Multi-Stage sampling. The instruments for data collection were a 16-item researcher-developed questionnaire, titled “Awareness of Food Security Needs and Causes of Global Hunger Questionnaire (AFSNCGHQ) and Focus Group Discussion (FGD). Data collected were analyzed using mean and standard deviation for research questions, while t-test statistics was used to test the two null-hypotheses at 0.05 level of significance. The findings based on the research questions, among others, indicated that: Women are aware of food security needs in South - East, Nigeria to a high extent and that the cuses of global hunger in South - East, Nigeria include high rate of population growth, prevalence of natural disasters such as flood, drought and climate change, inadequate provision of educational facilities for farmers to upgrade their skills for productive growth. Findings based on the test of null hypotheses revealed that: there was a significant difference in the mean ratings of the literate and non-literate women on the extent to which they are aware of food security needs and causes of global hunger in South - East, Nigeria .The following recommendations were made ;consistent and adequate effort should be made towards educating non-literate women on food security needs, especially on the prevalence of malnourishment in the communities ; adequate provision of educational facilities should be made available to farmers in order to upgrade their skills for productive growth and other ways of overcoming global hunger.